Reconstruction of Severe Neck Scar Contracture After Electrical Injury. Issue 1 (15th July 2021) - Xiao, Haitao; Liu, Ruolin; Liu, Xiaoxue; Wang, Huaisheng; Cen, Ying; Xu, Xuewen
Abstract : Abstract: High-voltage (≥1000 V) electrical injury is always related to high mortality and poor prognosis. The incidence rates of the high-voltage electrical injuries of the neck are lower than those of the other parts of the body. This article reports a case of the reconstruction of severe neck scar contracture after electrical injury. Compared with cases of scar contractures caused by nonelectrical injuries, this case had the following remarkable characteristics: extremely severe difficult airway, contracture scars involving whole layers of tissue, muscle and nerve damage, mandibular retraction, and poor occlusal relationship. The chief complaints of the patient upon admission, including forced position and continuous salivation, were greatly relieved through several operations by using different kinds of flaps and offering support to the flap from the palmar tendon and relocated mandible. However, the problem of salivation was incompletely solved. This problem might be caused by damage to related nerves and masticatory muscle function caused by high-voltage electrical injury. The patient was satisfied with the recovery of his appearance and movement function.